Comparison of 27-Gauge and 25-Gauge Microincision Vitrectomy Surgery for the Treatment of Vitreoretinal Disease: A Systematic Review and Meta-Analysis - Jinlan Ma; Qing Wang; Haoyu Niu (Journal of Ophthalmology)
Background. We performed a systematic review and meta-analysis to evaluate the safety and effectiveness of 27-gauge (27-G) microincision vitrectomy surgery (MIVS) compared with 25-guage (25-G) MIVS for the treatment of vitreoretinal disease. Methods. A systematic electronic search was conducted in March 2020 in PubMed, Embase, and the Cochrane library. Eligible criteria for including studies were controlled trials comparing 27-G vitrectomy with 25-G vitrectomy in patients with vitreoretinal disease. The main outcomes included operation time; best corrected visual acuity (BCVA) in logMAR; postoperative intraocular pressure (IOP); primary anatomical success rate for rhegmatogenous retinal detachment (RRD) cases and postoperative central macular thickness (CMT) for idiopathic epiretinal membrane (ERM) cases; intraoperative/postoperative complications. Odds ratio (OR) and mean difference (MD) were synthesized under fixed or random effects models. Results. Eleven studies enrolling 940 eyes were identified. Among those 11 studies, six studies were on the treatment of RRD and five studies were on the treatment of ERM, so subgroup analyses were conducted. The total pooled results indicated that 27-G surgery system had obvious advantages in improving BCVA at six months after the vitrectomy (P = 0.004) and reducing intraoperative/postoperative complications (P = 0.03). However, the mean operation time was significantly longer by three minutes for 27-G compared with 25-G vitrectomy (P = 0.002). In subgroup analyses, for the treatment of ERM cases, 27-G group was associated with less complications and longer operation time. However, for the treatment of RRD cases, 27-G groups and 25-G groups were comparable in operation time, postoperative BCVA, postoperative IOP, and primary anatomical success rate. Conclusions. This meta-analysis confirmed that 27-G MIVS was an effective and safe surgical system compared with 25-G MIVS for the treatment of RRD and ERM cases, even though 27-G system needs a longer surgical time.